Reporting Bias - Fischer, Paul E.; Verrecchia, Robert E. (The Accounting Review, 2000)
We present a simple model of managerial reporting bias for a setting in which the capital market is uncertain about the manager's reporting objective. In this setting, the manager's reporting bias reduces the value relevance of the manager's report; that is, it adds noise to the report. Through comparative static results, our model yields insights into factors that affect the slope and intercept terms in a regression of price on earnings. Specifically, we find that the information content of the manager's report, as captured by the earnings slope coefficient, falls as the private cost to the manager of biasing reports falls, and as the uncertainty about the manager's objective increases. We also find that the magnitude of the adjustment for the expected amount of bias, as captured by the absolute value of the intercept, falls as the uncertainty about the manager's objective increases. Finally, to highlight conditions under which managers would lobby to retain an option to bias reports (i.e., retain reporting flexibility), we analyze the effect of the option to bias on the manager's welfare. For example, we show that the ex ante benefit from biasing the report is positive if there is sufficient uncertainty about the manager's reporting objective.